Mitral valve prolapse: where is the missing link? - Antoine, Clemence; Michelena, Hector I.; Enriquez-Sarano, Maurice (Journal of Thoracic Disease; Vol 8, No 9 (September 28, 2016): Journal of Thoracic Disease, 2016)
Mitral valve prolapse (MVP), is the most common cause of primary mitral regurgitation but remains the subject of debates and gaps of knowledge regarding diagnostic criteria, prevalence and outcome. Diagnostically, the debate appeared settled in the 1980’s after the seminal description by Levine et al. of mitral annulus saddle shape and its influence on MVP diagnosis by echocardiography (1). MVP has since been defined by systolic override of one or both mitral leaflets ≥2 mm above the mitral annulus plane in parasternal long axis or apical 3 chambers view. Prevalence of MVP, based on those criteria, subsequently was estimated around 2.4% of the general population (2).